Association Between Baseline Therapy and Flare Reduction in Mepolizumab-Treated Patients With Hypereosinophilic Syndrome - Reiter, Andreas; Lefevre, Guillaume; Cid, Maria C.; Kwon, Namhee; Mavropolou, Eleni; Yancey, Steven W.; Steinfeld, Jonathan (Frontiers in Immunology, 2022)
Background Current standard-of-care treatments for hypereosinophilic syndrome (HES) include oral corticosteroids (OCS) and immunosuppressive/cytotoxic (IS/CT) therapies. The anti-IL-5 monoclonal antibody mepolizumab has also recently been approved for patients with this disease. The objective of this analysis was to assess the relationship between baseline therapy and flare reduction in patients with HES treated with mepolizumab, using data from the Phase III 200622 study (NCT02836496). Methods In the double-blind, parallel-group 200622 study, eligible patients were ≥12 years old and had HES for ≥6 months, ≥2 flares in the previous 12 months, blood eosinophils ≥1000 cells/μL at screening and ≥4 weeks’ stable HES therapy. Patients were randomised (1:1) to receive mepolizumab 300 mg subcutaneously or placebo every 4 weeks for 32 weeks plus their existing HES therapy. This post hoc, descriptive analysis assessed the effect of baseline HES therapy (IS/CT [±OCS], OCS No IS/CT, and No IS/CT/OCS) on the proportion of patients with ≥1 flare during the study period, the annualised rate of flares, time to first flare, and the proportion of patients with ≥1 flare during Weeks 20─32, with mepolizumab versus placebo. Results Mepolizumab treatment was associated with a decrease in the proportion of patients who experienced ≥1 flare during the study period in all baseline therapy groups versus placebo (32–96% reduction). Similarly, the probability of a flare was lower with mepolizumab (14.3–31.4%) than placebo (35.7–74.1%) in all baseline therapy groups, as was the annualised flare rate (0.22–0.68 vs 1.14–1.62). The proportion of patients who experienced ≥1 flare during Weeks 20–32 was reduced with mepolizumab versus placebo for all baseline therapy groups (55–85% reduction). For all endpoints, the greatest effect of mepolizumab treatment was seen in the IS/CT (±OCS) group. Conclusions Patients with poorly controlled HES are likely to achieve clinical benefit with mepolizumab in terms of flare reduction, regardless of their baseline therapy. Registry: https://clinicaltrials.gov/ct2/show/NCT02836496